PENAL MEDIATION BY POLICE INSTITUTION IN HANDLING HATE SPEECH THROUGH ELECTRONIC MEDIA: A LEGAL EFFORTS TO RESOLVE WITH A RESTORATIVE JUSTICE APPROACH - Toni Harmanto; Bagus Oktafian Abrianto; Xavier Nugraha (Universitas Dharma Wacana, 2022)
In the era of the industrial revolution 4.0 which caused the information to be easily spread, it turned out to have a bad impact, which led to the birth of the post-truth era. The post-truth era is an era in which objective facts become blurred because of broad public opinion. This makes it easy to spread hooks and expressions of hatred in society. The high perpetrators of hoax distribution and expressions of hatred make a legal solution needed that not only focuses on the deterrent effect for the perpetrators but the recovery of the community in its original condition. To restore the community's condition to its original condition, a restorative justice approach is used, one of which is through mediation by the police. This article will discuss, firstly related to the concept of mediation of penalties by the police in Indonesia and secondly it will discuss the approach of mediation of penalties by the Indonesian police in the handling of criminal acts of hate speech in electronicmedia. This article is a legal article that uses a statute approach, conceptual approach, and case approach. Based on the analysis in this article, it was found first the police nowdasy have an authority to solve the problem with restorative justice secondly that the first approach that pollice need to use in handling hate speech is by mediating in order to realize restorative justice by police agencies in Indonesia.